In search of finalizing and validating digital learning tools supporting all in acquiring full literacy - Lyytinen, Heikki; Louleli, Natalia (Frontiers in Psychology, 2023)
Unlike many believe, accurate and fluent basic reading skill (ie. to decode text) is not enough for learning knowledge via reading. More than 10 years ago a digital learning game supporting the first step towards full literacy, i.e., GraphoGame (GG) was developed by the first author with his colleagues in the University of Jyväskylä, Finland. It trains the acquisition of basic reading skills, i.e., learning to sound out written language. Nowadays, when almost everyone in the world has an opportunity to use this GG, it is time to start supporting the acquisition of full literacy (FL). FL is necessary for efficient learning in school, where reading the schoolbooks successfully is essential. The present plan aims to help globally almost all who read whatever orthography to start from the earliest possible grade during which children have learned the mastery of the basic reading skill to immediately continue taking the next step to reach FL. Unlike common beliefs, support of FL is mostly needed among those who read transparent orthographies (reading by the majority of readers of alphabetic writings) which are easier to sound out due to consistency between spoken and written units at grapheme-phoneme level. This makes readers able to sound any written item which is pronounceable with only a little help of knowing what it means. Therefore, children tend to become inclined to not pay enough attention to the meaning but concentrate on decoding the text letter-by-letter. They had to learn from the beginning to approach the goal of reading, mediation of the meaning of the text. Readers of nontransparent English need to attend morphology for correct sounding. The continuing fall of OECD’s Program for International Student Assessment (PISA) results, e.g., in Finland reveals that especially boys are not any more interested in reading outside school which would be natural way to reach the main goal of reading, FL. What could be a better way to help boys towards FL than motivating them to play computer games which requires reading comprehension. The new digital ComprehensionGame designed by the first author motivates pupils to read in effective way by concurrently elevating their school achievements by connecting the training to daily reading lessons. This article describes our efforts to elaborate and validate this new digital tool by starting from populations of learners who need it most in Africa and in Finland.